Additions to Gastropoda from the Peruvian sea - Paredes, Carlos (2011)
The following species of Gastropoda are recorded for the first time for Peruvian waters: Sthenorytis turbinus Dall, 1908, Crucibulum (Crucibulum) umbrella (Deshayes, 1830), Favartia (Murexiella) lappa (Broderip,1833), Cantharus (Cantharus) shaskyi Berry, 1959, Cantharus (Solenosteira) macrospira (Berry, 1957), Cancellaria (Bivetopsia) haemastoma Sowerby, 1832.